Museum as an Information Institution towards to 21st Century - Uralman, N. Hanzade (Information World, 2006)
At the beginning of the 21st century, museums are influenced by the conditions that had been shaped in the previous century in the context of their accessibilty to public. One of these methods, which is the most common one, is using information in their work and services. This method, prevents museums from being just show and recreation centers, supporting their service in the developing society. In this article, a classification has been suggested for museums defining, how information can be used in museums of our age to analyse their use of information.
Keywords: Museum information services; Museum information systems; Museums-Information processing